2019
DOI: 10.1002/admi.201801318
|View full text |Cite
|
Sign up to set email alerts
|

Directed and On‐Demand Alignment of Carbon Nanotube: A Review toward 3D Printing of Electronics

Abstract: Carbon nanotubes (CNTs) are 1D nanostructured materials with unique mechanical, optical, and electrical properties which can be potentially exploited for fabricating wide variety of devices. In addition, the biocompatibility of CNTs makes it attractive for wearable and implantable technology applications. Well‐aligned CNT structures show enhanced properties such as superior electron mobility, strain sensitivity, better mechanical property, and enhanced performance and reproducibility that are absent in their d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
82
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(84 citation statements)
references
References 310 publications
0
82
0
2
Order By: Relevance
“…In-situ alignment techniques include methods to achieve CNT alignment during the growing process, while ex-situ alignment techniques are implemented during the integration process of the CNTs [19]. Ex-situ alignment techniques include the use of electric fields [20,21], magnetic fields [22], surface forces [23], acoustic waves [24], mechanical stretching [25], and extrusion-based methods such as three-dimensional (3D) printing [26]. These techniques have proved useful to improve the CNT alignment in a chosen direction, often significantly enhancing the electrical conductivity of the nanocomposite in the aligned direction of the heterogeneous microstructures [27].…”
Section: Introductionmentioning
confidence: 99%
“…In-situ alignment techniques include methods to achieve CNT alignment during the growing process, while ex-situ alignment techniques are implemented during the integration process of the CNTs [19]. Ex-situ alignment techniques include the use of electric fields [20,21], magnetic fields [22], surface forces [23], acoustic waves [24], mechanical stretching [25], and extrusion-based methods such as three-dimensional (3D) printing [26]. These techniques have proved useful to improve the CNT alignment in a chosen direction, often significantly enhancing the electrical conductivity of the nanocomposite in the aligned direction of the heterogeneous microstructures [27].…”
Section: Introductionmentioning
confidence: 99%
“…D. Zhang et al already reported the preferential orientation that experienced GNPs during 3D printing [41]. This statement is also supported by Goh et al [42], who corroborated the alignment of CNTs along the extrusion direction. In order to study the anisotropy of the 3D printed parts, the surface electrical conductivity was measured along the X-axis (0 • ) and Y-axis (90 • ).…”
Section: Influence Of 3d Printing Operational Parameters On the Electmentioning
confidence: 52%
“…Current conventional electronics fabrication methods comprise of a series of additive and subtractive manufacturing techniques which are complicated, time‐consuming, uneconomical, and environmentally unfriendly. Therefore, 3D printing of electronics aims to mitigate these shortfalls and at the same time, allowing low‐cost fabrication of electronics and helps to increase designs freedom by allowing electrical circuits and components to be directly fabricated onto various types of substrates …”
Section: Introductionmentioning
confidence: 99%